From Bureaucratic and Quasi‐Market Environments: On the Co‐Evolution of Public Sector Business Process Management - Niehaves, Björn; Plattfaut, Ralf (Electronic Government - 9th IFIP WG 8.5 International Conference, EGOV 2010, Lausanne, Switzerland, August 29 - September 2, 2010. Proceedings, 2010)
Business Process Management (BPM) can be viewed as a set of techniques to integrate, build, and reconfigure an organization’s business processes for the purpose achieving a fit with the market environment. While business processes are rather stable in low-dynamic markets, the frequency, quality, and importance of process change amplifies with an increase in environmental dynamics. We show that existing designs of public sector BPM might not be able to cope with the mounting frequency and quality of business process change. Our qualitative in-depth case study of a local government suggests that a major cause for such misfit lies in ineffective organizational learning. We contribute to the literature by applying the Dynamic Capability framework to public sector BPM in order to better understand shifts in market dynamics and their consequences for BPM effectiveness. Practitioners find a proposal for identifying, understanding, and reacting to a BPM-misfit and for developing effective BPM strategies.